IDENTIFIKASI DAN PENENTUAN KADAR SENYAWA KURKUMIN PADA RIMPANG KUNYIT - Elizarni Elizarni; Willy Febri Yanti (Politeknik ATI Padang, 2019)
Turmeric is one type of medicinal plant that has many benefits and is found in many parts of Indonesia. The part that is often used as medicine is the rhizome. Turmeric rhizome is used for anticoagulants, antiedemics, decreased blood pressure, stomach ache and malaria medicine. The main chemical component in turmeric is curcuminoid. Curcuminoid consists of 3 fractions, namely curcumin, demetoksikurkumin, bis-demetoksikurkumin. The main fraction that exists in curcuminoids is curcumin. In this study an assessment and determination of levels of curcumin composition in the turmeric rhizome was carried out. Curcumin compound identification was carried out by TLC method using the chloroform: methanol (95: 5) mobile phase and silica gel stationary phase. The results obtained are 3 spots from standard bottling and samples with Rf values of the sample answer the standard Rf. Meanwhile, to determine the levels of curcumin compounds, the Uv-Vis spectrophotometric method was used. Measuring absorbance at a wavelength of 425.0 nm. And the results obtained levels of 6.71 % were collected. The results obtained are in accordance with the standards set by Pharmacopoeia Indonesia, which is not suitable from 6.60 %.